Law No. 184 of the Year 2023 Amending Certain Provisions of the Law on the Development of Micro, Small and Medium-Sized Enterprises, As promulgated by Law No. 152 of the Year 2020 = - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic